PENERAPAN TOTAL QUALITY MANAGEMENT (TQM) DALAM MENINGKATKAN MUTU PENDIDIKAN (Studi Kasus di STAIN Watampone) - SARIL SARIL (Program Studi Manajemen Pendidikan Islam IAIN Bone, 2017)
This Thesis studies about application of Total Quality Management (TQM) in improving education quality (an experimental sudy at STAIN Watampone). The perfuse of this research is to know the application of Total Quality Management (TQM) in improving education quality in STAIN Watampone. The main problem of this research is application of Total Quality Management (TQM) and the increasing of education quality in STAIN Watampone?. What about the concept of Total Quality Management (TQM) in improving the education quality and what about the prospect of (challange and oppurtunity) Total Quality Management (TQM) in improving education quality in STAIN Watampone.This research is a field research by using qualitative method with a observation technic, interview, and documentation. Analysing the data process is using normative approach, sosiologycal approach, pedagocical approach and management approach. Then the Total Quality Management (TQM) more little which is not sampled because of population, but the first total informan is more little getting increase to the data needed.The result of the research refers to the education quality in STAIN Watampone refers to the education quality is enough enable by STATUTA and academic orientation. The educational quality STAIN Watampone refers to superiority of human resource quality of implementation of state collage is STAIN area. Concept, principle, and application TQM that aplicated in STAIN Watampone as principle refers to leadership concept that to try influencing, moving on, and directing the people to cooperative in reaching the one purpose that appropriate in reaching with standard quality which have decided by STATUTA and academic orientation STAIN Watampone. In the future, STAIN Watampone can change status from STAIN to be IAIN or University certainly, they can change the abstract be a challange that must realizated.Base on the result of the research, there are implication and recommendation to the competen side by improving learner process the future. There are by application of Total Quality Management (TQM) is hoped being able to improving educational quality in a educational institute to the Total Quality Management (TQM) must focus by stakeholder. By institute, expecially STAIN Watampone is hoped can apply TQM concept thay can will produce output give significant influence in qualitative method although by quantitative method.